AN EMPIRICAL STUDY ON THE EFFECTS OF ADVERTISEMENT ON CONSUMER BEHAVIOUR - Ms. Lavael selsiya, Dr.Murugan Ramu (International Journal of Advanced Science and Technology, 2020)
Advertisements play an important role in the dynamic behavior and attitude of the buyers towards the goods displayed in the advertisements. Advertisements Change the way a consumer sees a product. Advertising is a way by which manufactures convince the people to buy their products. It is considered vital for the growth of the economy in a way. The current paper is based on stratified random method of sampling and the sample size is limited to and survey is taken on Chennai only and most importantly the survey was made in an authenticated way for appropriate result and also tries to reveal the effects of advertising on the buyers behaviour .This paper also includes various secondary sources to get through the current issues ,but the result will be focused mainly on the primary data.There were a total of 975 respondents (which included employers, employees,entrepreneurs , business men and the general public) to whom the survey questions were asked. The results are formulated and the hypothesis has been either proven or altered as any research should be. The tools used for the research include Statistical Tool for Social Sciences (SPSS).